(untitled) (Journal of actual problems of jurisprudence, 2018)
This article considers the legal regulation of investment activity in the field of land relations and land resources. The questions of the introduction or improvement of land and investment legislation, with a view to the rational use of land resources and land use for profit, and the national legislation of the Republic of Kazakhstan in this area requires changes that can create powerful market incentives and encourage investment in this sector. Key words: legal regulation, land, investment activity.